K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

12 tháng 6 2016

x -2xy+y=0

<=> 2x - 4xy + 2y = 0

<=> 2x - 4xy + 2y - 1 = -1 

<=> (2x - 4xy) - (1 - 2y) = -1 

<=> 2x(1 - 2y) - (1 - 2y) = -1 

<=> (2x - 1)(1 - 2y) = - 1 

Tới đây bạn lập băng ra nhé

12 tháng 6 2016

x -2xy+y=0

<=> 2x - 4xy + 2y = 0

<=> 2x - 4xy + 2y - 1 = -1 

<=> (2x - 4xy) - (1 - 2y) = -1 

<=> 2x(1 - 2y) - (1 - 2y) = -1 

<=> (2x - 1)(1 - 2y) = - 1 

29 tháng 7 2015

b) (x-7).(y+5)=0

=> x-7=0 hoặc y+5=0

  • Với :x-7=0 =>x=0+7 =>x=7
  • Với :y+5=0 =>y=0-5 =>y=-5